2005
DOI: 10.1111/j.1529-8817.2005.00208.x
|View full text |Cite
|
Sign up to set email alerts
|

Golli‐MBP Copy Number Analysis by FISH, QMPSF and MAPH in 195 Patients with Hypomyelinating Leukodystrophies

Abstract: Summary The inherited disorders of CNS myelin formation represent a heterogeneous group of leukodystrophies. The proteolipoprotein (PLP1) gene has been implicated in two X‐linked forms, Pelizaeus‐Merzbacher disease (PMD) and spastic paraplegia type 2, and the gap junction protein α12 (GJA12) gene in a recessive form of PMD. The myelin basic protein (MBP) gene, which encodes the second most abundant CNS myelin protein after PLP1, presents rearrangements in hypomyelinating murine mutants and is always included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…In assessing pathological deletions or duplications of single-copy genes, relatively simple multiplex fluorescent PCR methods (1517) have delivered an acceptable level of accuracy in this range. Multiplex fluorescent PCR methods compare the amount of PCR product made from a test amplicon with the yield from a reference locus in the same multiplex reaction.…”
Section: Introductionmentioning
confidence: 99%
“…In assessing pathological deletions or duplications of single-copy genes, relatively simple multiplex fluorescent PCR methods (1517) have delivered an acceptable level of accuracy in this range. Multiplex fluorescent PCR methods compare the amount of PCR product made from a test amplicon with the yield from a reference locus in the same multiplex reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Our Q-PCR method is fast and has reasonably high throughput; 25 samples can be analyzed in 2 h. Unlike other quantitative PCR methods, such as QFM-PCR, comparative multiplex PCR, and quantitative multiplex PCR of short fluorescent fragments, the real-time method does not require handling of PCR products, which reduces the potential for contamination of future reactions (Inoue et al 1996;Woodward et al 1998;Mimault et al 1999;Vaurs-Barriere et al 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Recently, two novel techniques, MLPA and MAPH, were proposed for reliable PLP1 dosage testing, allowing detection of small intragenic PLP1 rearrangements (demonstrated for MAPH) and detection of three or more PLP1 copies (demonstrated for MLPA) (Vaurs-Barriere et al, 2006;Wolf et al 2005;Combes et al 2006). The detection of partial rearrangements using a single real-time Q-PCR is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas Olig1-null mutant mice display only a delay in oligodendrocyte maturation, analysis of Olig2-null mutants demonstrated an absence of oligodendrocyte precursors (OLPs) in the spinal cord and a small number of OLPs in the different brain areas as well as a total absence of somatic motor neurons [Lu et al, 2002]. Additionally, loss-of-function studies in zebrafish indicated that the fish Olig2 homolog has a conserved role in development of both oligodendrocytes and motor neurons [Park et al, 2002].In order to test the potential involvement of OLIG2 in hypomyelinating leukoencephalopathies of unknown etiology, we selected three patients (from three independent families) from our large cohort of PMLD patients [Vaurs-Barrière et al, 2006]. These three patients all present with a severe and diffuse hypomyelination on brain MRI unexpectedly associated with a lower motor neuron involvement on electromyography (EMG) analysis.…”
mentioning
confidence: 99%